Strukturwandlungen und Standortverlagerungen in der japanischen Perlzucht - Aymans, Gerhard (ERDKUNDE, 1965)
The location of practically all the early pearl farms (1910-1925) in Japan depended mainly on the availability of diving gatherers, who alone could cope with the difficult work at sea, outside the pearl farms proper. Gradually, however, the importance of this specialist labour force diminished, since the pearl cultivators developed new techniques, which made the laborious diving unnecessary. This led to several early changes, both in the location and in the layout of pearl farms. The structure of the pearl industry was for a long time (1910-1945) determined by the monopolistic attitude of its founders, who kept the production of pearls strictly closed to all but a few newcomers. This policy influenced the spatial distribution and the location of pearl farms, too. The most radical changes took place after the war, when the Japanese government came out with its gigantic reform of the primary industries. Henceforth the cultivation of pearls, too, was at least in principle open to all who had the necessary experience. This led not only to an ever growing number of pearl farms, particularly in the hands of fishermen, but also to many new techniques of using the coastal waters. The most spectacular and economically most important innovation was the use of several cultivation grounds in different seasons and for different purposes. This made pearl farming change from a residentiary to a highly mobile branch of marine farming. Although pearl farming as a whole is expanding faster than any comparative industry, many cultivators seem quite unable to adapt themselves to the more and more competitive development. This is particularly true of those fishermen who only took to pearl farming within the last couple of years. Generally speaking one can say that the family farms are falling behind, because they are practically, though not legally, confined to the overcrowded traditional grounds. The larger companies, on the other hand, are pushing foward, because they have the capital to develop the more promising waters. In doing this they take every care not to spread their knowledge among the local fishermen, for these would - under the protection of the post-war legislation - certainly use such knowledge to the disadvantage of the pioneering companies. Under the pre sent technical and economic circumstances pearl cultivation in the future will be a matter not of family farms, but of larger companies, although there is a certain amount of government action to the contrary. Whether these larger units will be stock companies or cooperative companies remains to be seen, but a new locational pattern is already emerging from this very recent development.